Implementação de um controlador ODL para SDN - Souza, Gustavo Carneiro de (2019)
By the exponencial growth of technology and computer networks, there is a need to expand and / or modernize these network environments, either to upgrade devices or make them simpler and more pratical to manage. However, the stuck management of some devices makes this control difficult, where the source code is closed, and it is not possible to change at the user level, only by the supplier. This way, the Software Defined Networking (SDN), hosted by the Linux Foundation, an open source software, with a broad academy of developers, members and collaborative entities, which aims to bring solutions to these problems. It has a multi-layered architecture, where data, administration and control plans are basically separated, having at their extremes APIs that connect with routers, switches and various protocols, such as the well-known Openflow. Thus, this paper aims to briefly explain some controllers such as Open Network Operating System (ONOS), Floodlight and RYU, to demonstrate the installation and implementation of a virtualized OpenDaylight (ODL) controller in Virtualbox and a Mininet to give the possibility of creating a topology with the switch’s envirionment, allowing for homologation testing for later production use. Finally, show some forms of network management, what you can do and where to find both as the controller as Mininet, exemplifying the importance of having a whole network in one place, centralized, highlighting one of the main features of the SDN controller.